Implementation of Contextual Learning to Increase Learning Motivation at PKBM - Dewanti, Lintang Kirana Putri; Shofwan, Imam (Jurnal Penelitian Pendidikan, 2025)
The problem of low motivation and involvement of learning community in learning at PKBM is the background of this research, due to the learning approach that is still conventional and less contextualized. This study aims to describe the implementation of contextual learning in English subjects and analyze its impact on the learning motivation of PKBM residents. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews and documentation of six respondents. The results show that CTL is implemented through planning based on the social context of the learning community, implementation that utilizes discussion methods, hands-on practice, digital media, and evaluation that is participatory and authentic. This approach is proven to encourage increased learning motivation in the six main aspects. The implication of this research shows the importance of integrating experiential learning in non-formal education. The novelty of this research lies in the application of CTL in the context of equivalency education, which has not been widely studied, especially in English subjects. This research not only makes a practical contribution in strengthening pedagogical practices, but also expands the theoretical understanding of the application of CTL in equality education that is inclusive and oriented towards empowering learning citizens.